2012
DOI: 10.7439/ijbar.v3i4.425
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Prostate Specific Antigen for Detection of Prostatic Lesions

Abstract: Background: Carcinoma of prostate is one of the common tumors of old age in men. With digital rectal examination (DRE), prostate specific antigen (PSA) is a major screening tool for prostate cancer. The cutoff value for PSA of 4.0 ng/mL gives the highest sensitivity and highest specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
8
2
Order By: Relevance
“…This is in agreement with the mean age reported by multiple studies including Khant et al (66.9 ± 9.4 years), 10 Josephine (65.5 years), 11 and Lakhey et al (67.6 years)12 in Indian and Nepalese patients respectively. In comparison, Jasani and colleagues reported mean age of 57.77±4.86 years for patients with BPH and 65.82±5.6 years for patients with prostate cancer 13. In our study, BPH was diagnosed in 1676 (76.56%) patients, prostatitis in 133 (6.07%), Carcinoma in 378 (17.26%) and PIN in 02 (0.09%) patients only.…”
contrasting
confidence: 44%
“…This is in agreement with the mean age reported by multiple studies including Khant et al (66.9 ± 9.4 years), 10 Josephine (65.5 years), 11 and Lakhey et al (67.6 years)12 in Indian and Nepalese patients respectively. In comparison, Jasani and colleagues reported mean age of 57.77±4.86 years for patients with BPH and 65.82±5.6 years for patients with prostate cancer 13. In our study, BPH was diagnosed in 1676 (76.56%) patients, prostatitis in 133 (6.07%), Carcinoma in 378 (17.26%) and PIN in 02 (0.09%) patients only.…”
contrasting
confidence: 44%
“…Electrolyte imbalance has been severally observed as the commonly identified complication in severe cases of malaria. Electrolyte imbalance acts as an indicator for the level of disease virulence due to its close association with the severe P. falciparum and P. vivax malaria (16). In this study, blood samples were used for the evaluation of electrolytes in malaria patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in Na level can result in several health conditions (17).Various literature shows reports of increased vasopressin(ADH) secretion which either appropriately or inappropriately is a key factor in the reduced level of sodium in malaria, as sodium is able to gain entry into the infected cells and cause loss of blood (18). Hyponatraemia has been identified as a common outcome of malaria (16). Ikekpeazu et al also reported a significant lowering of sodium and Potassium levels in malaria infection (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a PSA value greater than 4 ng/mL, irrespective of DRE results, generally undergo biopsy. 9 Aims and Objectives (i) To study prevalence of distribution of various prostatic lesions, in the region of Dakshina Kannada (Karnataka). (ii) To evaluate the utility of PSA assay as a method of investigation in diagnosis of prostatic lesions.…”
mentioning
confidence: 99%